Determinación del contenido de compuestos bioactivos y estudio de las propiedades antioxidantes en extractos de mora andina (Rubus glaucus Benth) de Ecuador - Armijos Montesinos, Daniela Stefanía (2018)
The blackberry (Rubus glaucus benth) is the red fruit of high consumption appealing for its exotic flavor around the world. Its native production is found in the tropical zones of America and, in Ecuador, throughout the Andean area of the country. Blackberry fruits, in comparison with other red fruits, are appreciated for possessing bioactive compounds which beneficial effects in human health, especially for their ability to prevent diseases linked to oxidative stress. In this study, a complete chemical characteristic of the berries collected from Machachi, Cayambe and Ambato was proposed, for which quantitative techniques were used for determine compounds of interest such as, total polyphenols, flavonoids, tannins, anthocyanins, β-carotene, vitamin C as well as an identification of the most representative phenolic acids through the highpressure liquid chromatography coupled to mass spectrometry. In addition, the determination of the antioxidant capacity of frutis was carried out by the ferric reducing antioxidant power (FRAP) and DPPH method of antioxidant assay. The results obtained reveal that the samples studied have a similarity in the content of phenols, flavonoids, anthocyanins and tannins, which differ only in the content of vitamin C and beta-carotene depending on the area. This study establishes the bases to promote the investigation of exotic ecuadorian fruits as well as providing knowledge for its therapeutic use.